Investigate The Relationship Between ICT Adoption and SME Performance with Digital Literacy Serving as A Mediator Variable Using TOE Framework - Uus Muhamad Husni Tamyiz; Munir Munir; Chairul Furqon; Puspo Dewi Dirgantari (Khazanah Sosial, 2025)
The current study investigates the relationship Information Communication Technology (ICT) and social media adoption, with Small Medium Enterprise (SME) performance in West Java, Indonesia, utilizing digital literacy as a mediator variable.   The Technology-Organization-Environment (TOE) paradigm was utilized in conjunction with Diffusion of Innovation (DOI) theory to evaluate the impact of nine technological, organizational, and environmental features on ICT adoption.  To collect data, an online questionnaire was distributed to 396 small business owners, executives, and supervisors in West Java, and the results were analyzed using Partial Least Squares Structural Equation Modeling. According to the findings, organizational and contextual variables had a substantial impact on both ICT acceptance as well as digital literacy, but technological factors only influenced ICT adoption. The study found that ICT usage improves SME performance both directly and indirectly through the mediation of digital literacy.  The study broadens the TOE framework by incorporating previously underutilized factors like interactivity, visibility, and the bandwagon effect, while also providing empirical evidence of digital literacy's critical role in improving the relationship between technology adoption and business performance.  These findings provide useful insights for SME stakeholders in emerging economies looking to capitalize on digital transformation for a competitive advantage, emphasizing the significance of complete digital literacy development alongside technology adoption efforts.